Characteristics of the Sarcoplasmic Reticulum Ca 2+ -dependent ATPase from Masticatory Muscles - Sánchez, Gabriel Antonio (2004)
We compared the sarcoplasmic reticulum (SR) Ca-ATPase from masseter (M) and medial pterygoid (MP) muscles with that from fast muscles (FM) to examine whether its calcium transport capability and enzymatic activity are different. SR vesicles from FM, M, and MP muscles were obtained according to Champeil et al.(1985). Assays for characterization of the enzyme properties were performed. The results showed similar optimal conditions for the Ca-ATPase activity and calcium transport in M, MP, and FM. However, the maximal values of calcium transport, Ca-ATPase activity, and Ki for thapsigargin were significantly lower in the masticatory muscles. These findings are likely related to different Ca-ATPase isoforms. Since the local anesthetics used in dentistry inhibit Ca-ATPase and calcium transport in FM, it will be important for the effects of these drugs on the Ca-ATPase of masticatory muscles to be assessed.